Identifying the Students’ Needs in Teaching Speaking to the Middle School Students in Pinrang Indonesia: Identifying the Students’ Needs in Teaching Speaking to the Middle School Students in Pinrang Indonesia - Haryanti, Tri; Nur, Rafiah (La Parole : Journal of Language Teaching and Pedagogy, 2021)
English is one of the subject that learners must be follow in Indonesia such as in play group, elementary school, junior high school, senior high school even in a college. It will have a long time for the students learn this subject. It still doesn't work as we hope, the students reason that their lack of speaking coming from the media of teachingteaching, ascribe from the teaching strategy and the material. It is found from pondok pesantren Darul Ulum Ath Thahiriyah paladang pinrang (2018), the teacher found that there are 95% students’ classification speaking is poor, and 5% fair in this school. Although the government and the expert had been put a big attention in this subject but a problem still occurring until today, therefore the researcher decided to involve a learning strategy on this paper, the researcher will analyze the students’ need to find out the problems, that can helps the students’ and teacher to be solve it It will analyze and formulate by long step and recur, besides it will be supporting by several sources such as the students, alumnus and the teacher, this research question is what are the students of SMPN 1 problems in teaching learning english ?The researcher had been applied apply a mixed method, quantitative and descriptive approaches. There are two instruments used, Interview and questioners. The finding is the teacher's interview said that students have a lack pay attention in learning this subject, it causes by the teacher strategy that unsuitable with the students' needs, it supports by some suggestion of the alumni, and students' expectation that they want to more variant in speaking activity. The students rarely hope to cover this because of it is the international language, several hope it can help to take a scholarship, some of them said because they want to abroad and speak with the native speaker, and most of them hope it can help their dream, their ambition, the researcher also has given four choices of media, these are a picture, video, song, and story, there are 8 students choose the story, 10 students choose the picture, 36 students choose song and 36 also choose video. The students’ lack occurring by the teaching learning process that unsuitable with them, they have lot of hopes in teaching learning as EFL Learner including students high expect to the activities in learning process are dominated by answer the question, students expect that they could participating in a conversation of English daily, they expect high to communicate with a native speaker, and of students expect to participating in class discussion using English to ask or answer question